PROMPT COMMUNITY BASED VETERINARY SERVICES DELIVERY SYSTEM AND ITS IMPACT ON DISEASE BURDEN AND PRODUCTION IN THE DAIRY ANIMALS - Khan; M. A.; A. Mahmood; M. Younus; F. Nazir (Journal of Animal and Plant Sciences, 2013)
The lack of animal health services is a major hindrance in the control of livestock diseases in Pakistan. Consequently decreased production is a major factor in poverty alleviation in a developing country like Pakistan, where small livestock owners are the backbone of agriculture. The present study is therefore designed to evaluate the effectiveness/efficiency of an alternative model of animal health services delivery system through community participation which will ultimately help in reducing disease burden and consequently increase livestock production. For this purpose two concurrently working veterinary services delivery systems i.e. conventional public based system and community based system were compared in terms of services delivery, epidemiological parameters and cost-benefit ratio of an average farmer for a period of one year from July, 2005 through June, 2006 in peri-urban areas of central Punjab. It was recorded that community based system has significant impact (P < 0.05) on epidemiological parameters (incidence rate, mortality rate and fertility rate), services delivery (vaccination, deworming, treatment and nutritional support) and cost- benefit ratio of an average farmer as compared to public based system. There was 50% decrease in incidence rate of economically important diseases in community based system as compared to public based system which was 16.75% and 36.43%respectively. Similarly the mortality rate in community based system was 0.65% less than the conventional public based system which was 3.53% and 4.18% respectively. An improvement of 12% in fertility rate was observed in community based system as compared to public based system which was 63% and 51% respectively. The average annual cost- benefit ratio per farmer was almost double than public based system. The delivery of services was much better in community based system as compared to public based system. From the present study it is concluded that community based veterinary services delivery system is helpful in reducing disease burden and will consequently boost the agricultural economy by increasing livestock production if replicated through out the country.
Keywords: community based veterinary services; herd health; fertility rate; epidemiological parameters